The Implementation of Task-Based Language Teaching Principles in Speaking Class - Khoerul Awwal, Tia; Meiristiani, Noeris; Rofiudin, Rofiudin (Cakrawala: Jurnal Pendidikan, 2022)
In teaching speaking for EFL, teacher has to consider a strategy that exposes students to speaking practices. This study aims to determine the implementation of Task-Based Language Teaching (TBLT) principles in English learning, especially speaking. The approach used was descriptive qualitative. The instruments were classroom observations and interviews and the research subjects were 1 English teacher and 25 students of Class IXA at Darunnajat Islamic Boarding School Bumiayu Brebes. This study reveals that the teacher has implemented the seven principles of TBLT namely scaffolding, task dependency, recycling, active learning, integration, reproduction, and reflection suggested by Nunan (2004) in teaching speaking. They were reflected in the activities that students experience in the classroom.